The relationship between various risk factors and the cost of equity premium implied by analysts' forecasts on the New York Stock Exchange - Goussard, Heleen (Department of Finance and Tax, 2018)
The cost of equity is used extensively for capital allocation decisions, and the various methods used to estimate it often result in materially different outcomes. A model of the impact of known risk factors on the implied cost of equity used by equity analysts, who are seen as informed market participants, could be a guideline and sense check for other professionals estimating cost of equity for capital allocation decisions. This study, an implementation of Arbitrage Pricing Theory, attempts to create a parsimonious model of factors that are associated with the implied cost of equity premium utilised by equity analysts on the New York Stock Exchange ("NYSE"). After limiting the sample to NYSE-listed companies that were primarily exposed to US macro-economic conditions and were likely to be valued overwhelmingly on a going-concern basis, the test sample consisted of 5,343 company quarters covering the period 2006 to 2015. In the first part of the methodology, sixteen factors identified from previous literature as possibly influencing the cost of equity were tested for their association with the implied equity risk premium, as calculated from analysts' two-year earnings forecasts and target share prices using the Easton-method. Only those factors that were statistically significantly associated with the implied cost of equity were retained for the second part of the methodology, in which mixed effects modelling and optimisation using the Akaike information criterion was used to find a parsimonious model linking the statistically most significant factors to the implied cost of equity. The final model could explain 40% of the variation in implied risk premium by the fixed effects (specified variables), and 62% when the random effects (observable effects of unspecified variables) were included. The study found that the risk free rate was most strongly (and negatively) associated with the size of the implied equity risk premium. Other factors that are statistically significantly associated with the implied equity risk premium are the two-year beta (+), the profitability dummy variable (-), return on equity (-), two-year share price volatility (+), long-term growth (+), Market momentum (+), and the debt to equity ratio (+). It was further found that not all factors which have historically been shown to influence returns are significantly associated with implied cost of equity estimates, which is contrary to expectations in a fully efficient market, where the only difference in the two would result from the information that changes cash flow expectations or the risk profile of the cash flows. This study contributes to the current body of literature on cost of equity in the following ways: • To the author's knowledge, this study combines a far wider array of factors of all types than any of the previous studies on the topic, and uses target prices rather than market prices to calculate the implied cost of equity premium. • The study uses the adaptive and recursive option valuation model to eliminate companies for which the testing would not be relevant. • The study used mixed effects modelling to measure the impact of the various factors on the cost of equity premium.